Programa educativo de interacción recíproca para mejorar la gestión de los conflictos sociales en directivos y docentes de la institución educativa Rosa Agustina Donayre de Morey Iquitos 2022 - Del Aguila Paredes, Kika (2025)
The research aim was to assess the effect of the reciprocal interaction educational program to improve the social conflict management between the managerial and teaching staff of the Rosa Agustina Donayre de Morey Educational Institution in Iquitos, 2022. An evaluative, longitudinal, field-based, and univariate methodological approach was adopted, involving a population of 70 individuals, with a sample distributed between an experimental group of 37 and a control group of 33. Data collection was conducted using surveys and written performance tests, which were validated by experts. The findings revealed that the participants in the experimental group, after the application of the program, exhibited a significant increase in the averages related to the management of social conflicts and their respective dimensions, compared to the control group, with averages of 14.05 and 10.37 respectively. These results demonstrate the effectiveness of the program in enhancing the conflict resolution skills of the educational staff, providing a significant reference for the design of future pedagogical interventions aimed at promoting a more harmonious school environment and efficiency in conflict resolution.